Genetic polymorphisms for BDNF, COMT, and APOE do not affect gait or ankle motor control in chronic stroke: A preliminary cross-sectional study. Issue 1 (2nd January 2021) - Aljuhni, Rehab; Cleland, Brice T.; Roth, Stephen; Madhavan, Sangeetha
ABSTRACT: Background : Motor deficits after stroke are a primary cause of long-term disability. The extent of functional recovery may be influenced by genetic polymorphisms. Objectives : Determine the effect of genetic polymorphisms for brain-derived neurotrophic factor ( BDNF ), catechol-O-methyltransferase ( COMT ), and apolipoprotein E ( APOE ) on walking speed, walking symmetry, and ankle motor control in individuals with chronic stroke. Methods : 38 participants with chronic stroke were compared based upon genetic polymorphisms for BDNF (presence [MET group] or absence [VAL group] of a Met allele), COMT (presence [MET group] or absence [VAL group] of a Met allele), and APOE (presence [ε4+ group] of absence [ε4- group] of ε4 allele). Comfortable and maximal walking speed were measured with the 10-m walk test. Gait spatiotemporal symmetry was measured with the GAITRite electronic mat; symmetry ratios were calculated for step length, step time, swing time, and stance time. Ankle motor control was measured as the accuracy of performing an ankle tracking task. Results : No significant differences were detected ( p ≥ 0.11) between the BDNF, COMT, or APOE groups for any variables. Conclusions : In these preliminary findings, genetic polymorphisms for BDNF, COMT, and APOE do not appear to affect walking speed, walking symmetry, or ankle motor performance in chronic stroke.